2015
DOI: 10.1007/s11013-015-9480-5
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood and the “Madness of Hunger”: “…Want Almal Vra vir My vir ‘n Stukkie Brood” (“…Because Everyone Asks Me for a Little Piece of Bread”)

Abstract: It is widely assumed that the social and economic conditions of poverty can be linked to common mental disorders in low-, middle- and high-income countries. Despite the considerable increase in quantitative studies investigating the link between poverty and mental health, the nature of the connection between poverty and emotional well-being/distress is still not fully comprehended. In this qualitative study, exploring how one group of Coloured South African women, diagnosed with depression and residing in a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Mozambican women have higher than expected rates of a positive depression screening, but similar levels of depression to Zambian women (Chipimo and Fylkesnes, 2009). As found in other low and middle income country-based studies (Bartels et al, 2002; Collins et al, 2015; Guerra et al, 2016; Magidson et al, 2016; Schneider et al, 2007), older women (Das et al, 2007; Guerra et al, 2016) and women who reported higher food insecurity (Kruger and Lourens, 2016; Patel et al, 1998; Tsai et al, 2016) or poverty (Patel et al, 1999; Patel and Kleinman, 2003; Todd et al, 1999) were associated with depression. The strong association of a positive depression screening with limited Portuguese language ability highlights the isolation likely experienced by those who cannot speak the national language.…”
Section: Discussionsupporting
confidence: 64%
“…Mozambican women have higher than expected rates of a positive depression screening, but similar levels of depression to Zambian women (Chipimo and Fylkesnes, 2009). As found in other low and middle income country-based studies (Bartels et al, 2002; Collins et al, 2015; Guerra et al, 2016; Magidson et al, 2016; Schneider et al, 2007), older women (Das et al, 2007; Guerra et al, 2016) and women who reported higher food insecurity (Kruger and Lourens, 2016; Patel et al, 1998; Tsai et al, 2016) or poverty (Patel et al, 1999; Patel and Kleinman, 2003; Todd et al, 1999) were associated with depression. The strong association of a positive depression screening with limited Portuguese language ability highlights the isolation likely experienced by those who cannot speak the national language.…”
Section: Discussionsupporting
confidence: 64%
“…In this way, society makes mothers with fewer resources more accountable for meeting a perceived “mother ideal” than mothers with more resources. Irrespective of a child’s health, being unsure of how she will fulfill her maternal role of feeding her child and/or fearing her child will be hungry is often accompanied by feelings of guilt, shame, or depression [ 32 , 33 ]. Overall, this background is critical to understanding feeding responsibility and child health in the context of food insecurity.…”
Section: The Role Of Motherhood and Feeding In The Context Of Foodmentioning
confidence: 99%
“…discussion food insecurity and emotional well-being This chapter highlights how food insecurity impacts parents' emotional well-being, and how economic hardship hampers parents' management of everyday life, making it hard to accomplish social expectations related to parental roles. While several studies show that food insecurity is associated with psychological distress, and may lead to common mental disorders, such as anxiety and depression (Jones 2017;Kruger and Lourens 2016), less is known about its effects on satisfaction with life. Beyond what is known to be a consequence of poverty and material deprivation, some issues seem specific to food insecurity, in the context of emotional well-being.…”
Section: Methods and Participantsmentioning
confidence: 99%
“…The negative impact of food insecurity on emotional well-being helps to explain why a higher prevalence of common mental disorders was found in families experiencing food insecurity, as stated above. In fact, several studies stress the relationship between food insecurity and depression and anxiety in mothers caused by psychological distress related with feeling unable to provide healthy food to their children (Kruger and Lourens 2016;Hadley and Patil 2006). Although a greater number of studies were conducted with women on account of being seen as families' primary caregivers, the same psychological effects were also found in men (Jones 2017; Althoff, Ametti and Bertmann 2016).…”
Section: Effects Of Materials Deprivation and Food Insecurity On Mentamentioning
confidence: 99%